Efficacy of cilostazol in promoting the maturation of newly created arteriovenous fistula in patients with end-stage renal disease: a systematic review and meta-analysis - Willim, Herick Alvenus; Sugandi, Erica; Rosa; Sani, Alvin Ariyanto; Khouw, Hengky (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Arteriovenous fistula (AVF) is considered the gold standard for vascular access in hemodialysis. However, achieving the successful maturation of AVF remains a challenge. Cilostazol, a phosphodiesterase-3 inhibitor, has shown promise in enhancing AVF maturation. This study aimed to assess the clinical efficacy of cilostazol in promoting AVF maturation. METHODS This meta-analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A comprehensive systematic literature search was performed using PubMed, ScienceDirect, Cochrane Library, ProQuest, and Google Scholar to identify studies investigating the efficacy of cilostazol on the maturation of newly created AVF in patients with end-stage renal disease and published up to August 2023. The intervention group received perioperative cilostazol therapy, while the control group did not receive cilostazol. The outcomes were the maturation rate of AVF and AVF-related complications. Meta-analysis was conducted using Review Manager software version 5.3. RESULTS 5 studies involving 549 patients were included. The intervention group comprised 228 patients, while the control group comprised 321 patients. In the pooled analysis, patients in the intervention group had a significantly higher rate of AVF maturation (odds ratio [OR] = 2.18, 95% confidence interval [CI]: 1.29–3.68, p = 0.003, I2 = 47%) and a lower rate of AVF-related complications (OR = 0.46, 95% CI: 0.28–0.77, p = 0.003, I2 = 27%) compared to the control. CONCLUSIONS Cilostazol was associated with a higher rate of AVF maturation and a lower rate of AVF-related complications.